CLOSING THE GAP: PROGRESSING FROM INJURY PREVENTION RESEARCH TO SAFETY PROMOTION PRACTICE. (7th October 2012) - Hanson, D; Finch, C; Allegrante, J; Sleet, D
Abstract : Background: The application of the public health model to injury prevention starts with: 1. establishing the magnitude of the problem 2. identifying risk factors 3. developing effective interventions 4. disseminating them Unfortunately most research does not result in widespread dissemination of effective interventions. Aims/Objectives/Purpose: This paper describes and addresses the barriers that impede the implementation of effective injury prevention interventions. Methods: Literature review. Results/Outcome: Several gaps between injury prevention research and safety promotion practice are identified:  the efficacy and effectiveness gap (a scientific problem),  the research to practice gap (an implementation problem),  the injury prevention to safety promotion gap (a political problem). These gaps stem from the contrasting approaches researchers, policy makers, practitioners and the community take to the scientific, practical, and social challenges posed by the contextual complexity of injury. Some researchers believe that stages 1–3 constitute the real scientific work of injury prevention arguing that Stage 4, dissemination and adoption, can essentially be delegated to practitioners who merely have to apply their research findings. This approach underestimates the importance of the contextual determinants of success. Significance/Contribution to the Field: Three types of experts are required to design effective interventions capable of dissemination into the wider community: researchers (content experts), practitioners (process experts) the target community itself (context experts). From the outset, an open transdisciplinary dialogue that synthesises the expertise of all stakeholders is required to design effective interventions that can be applied in the real world.